Electrical impedance tomography by elastic deformation - Ammari, H; Bonnetier, E; Capdeboscq, Y; Tanter, M; Fink, M (Society for Industrial and Applied Mathematics, 2008)
This paper presents a new algorithm for conductivity imaging. Our idea is to extract more information about the conductivity distribution from data that have been enriched by coupling impedance electrical measurements to localized elastic perturbations. Using asymptotics of the fields in the presence of small volume inclusions, we relate the pointwise values of the energy density to the measured data through a nonlinear PDE. Our algorithm is based on this PDE and takes full advantage of the enriched data. We give numerical examples that illustrate the performance and the accuracy of our approach.